Investigating the Safety Impact of Segment- and Intersection-Level Bicycle Treatments on Bicycle–Motorized Vehicle Crashes. Issue 2 (February 2023) - Deliali, Aikaterini; Fournier, Nicholas; Christofa, Eleni; Knodler, Michael
Bicycle treatments are installed to elevate motorists' awareness of the presence of bicyclists and to enhance bicycle safety and mobility. To date, no studies have compared the safety benefits of sharrows and protected- and conventional bike lanes, or intersection-level treatments like bike boxes and intersection-crossing pavement markings. One factor that limits bicycle safety research is the lack of adequate bicycle exposure data. For this study, a crowdsource app was used for estimating networkwide bicycle demand data for Portland, OR. Crash prediction models were developed for road segments and signalized intersections to associate bicycle treatment presence and type with crash frequency. Compared with the "no treatment" case, protected bike lanes (odds ratio [OR] = 0.032), sharrows (OR = 0.211), and conventional bike lanes (OR = 0.552) were safer for road segments. Signalized intersections where segment-level bicycle treatments exist at more than one of the intersecting roads were associated with higher crash frequency. Specifically, for signalized intersections with one conventional bike lane, with two conventional bike lanes, or with a conventional- and a protected bike lane, the respective CMFs were 1.94, 2.07, and 3.38. Signalized intersections with at least one bike box or intersection-crossing pavement markings experienced higher crash frequency than intersections with no treatments, however not necessarily in the approach where the treatment was located. The respective Crash Modification Factors (CMFs) were 1.39 and 1.76. The findings could guide practitioners in selecting bicycle treatments for segments, whereas the models for signalized intersections could identify intersections with high crash frequency that need safety improvements.